1994
DOI: 10.1159/000106744
|View full text |Cite
|
Sign up to set email alerts
|

A Scottish Record Linkage Study of Risk Factors in Medical History and Dementia Outcome in Hospital Patients

Abstract: The relative risk (RR) of acquiring a hospital diagnosis of dementia was estimated in 101,104 patients (1 in 25 fraction) randomly selected from total admissions to Scottish general hospitals between 1968 and 1977. The patients were allocated to putative at-risk groups according to main diagnosis at time of index admission, and RR of dementia (ICD 9290) was contrasted between ten risk groups and a reference group. Record linkage was used to reduce admission episodes to individual cases, to link general and psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Some show that head injury has a significant or nearly significant effect on AD risk, [1][2][3][4][5][6][7][8][9] whereas others show no association. [10][11][12][13][14] Among longitudinal studies, [15][16][17][18] only one 17 reported a significantly increased risk of developing AD in persons with head injury. A reanalysis of the Rochester Epidemiology Project data suggested that head injury may reduce the time to onset of AD.…”
mentioning
confidence: 99%
“…Some show that head injury has a significant or nearly significant effect on AD risk, [1][2][3][4][5][6][7][8][9] whereas others show no association. [10][11][12][13][14] Among longitudinal studies, [15][16][17][18] only one 17 reported a significantly increased risk of developing AD in persons with head injury. A reanalysis of the Rochester Epidemiology Project data suggested that head injury may reduce the time to onset of AD.…”
mentioning
confidence: 99%
“…Retrospective data from 1981 until conduct of survey interview provides information on hospital diagnoses of any pre-existing morbidity. Similar linkage had previously been carried out in a randomly selected sample of individuals admitted to Scottish general hospitals in the late 1960–1970s 12 and registered users of general practices in the mid-1980s 13 Table 2Data available according to each SMR scheme Code Record type SMR00OutpatientSMR01 a General/acute inpatient/day caseSMR02MaternitySMR04 a Mental health inpatient/day caseSMR06 a Cancer registerSMR11Neonatal dischargeSMR50Geriatric (long stay)

a Available in the minimum SHeS–SMR.

Figure 1Linkage of study members of the SHeSs to hospital discharge, cancer registry and mortality records
…”
Section: What Does It Cover?mentioning
confidence: 74%
“…The few examples of comprehensive record linkage systems include the Oxford Record Linkage Study (Acheson 1967;Goldacre, Shiwach and Yeates 1994), that applying these techniques on birth, death and hospital data of around 350,000 individuals allowed the study of associations between certain diseases, and using longitudinal matched data enabled the analysis of occupational mortality, migration and related socio-economic factors, the Scottish Record Linkage System (Kendrick and Clarke 1993;Ryan 1994), the Rochester Epidemiology Project (Melton 1996) and the Manitoba Population Health Information System Black, Burchill and Roos 1995).…”
Section: Record Linkagementioning
confidence: 99%